Carbon Nanotube (CNT) Composites and its Application; A Review - Mohammed Ridha H Alhakeem (ITScience (Information Technology and Science), 2022)
Due to their superior mechanical, thermal, electrical, and tri-biological characteristics, carbon nanotubes (CNTs) have been widely used in a variety of industries, from aerospace to energy, since their discovery in 1991. Their compact size, amazing tensile strength, and light weight They are often used as reinforcements in metals, plastics, and even additive manufacturing due to their popularity and conductivity. In this analysis, we present a list of these structures and an in-depth discussion of the CNT-reinforced materials can be processed using a variety of techniques, including chemical vapor deposition (CVD), ball milling, both laser melting and hot pressing. The restrictions in the production and processing of these composites additionally discussed, strengthened by many authored works. To comprehend how these composites' properties change in relation to other parameters, such as a wide range of variables, such as temperature, CNT length, diameter, etc. A summary is given, explaining various methods for performing experimental analysis and providing convincing arguments for putting the changes' causes in. Therefore, we investigate the specialized uses of these CNT-reinforced composites in industries like aerospace, energy, biomedicine, and auto, and how they can be handled further, altered to make room for less expensive and more effective fixes going forward.